A Strategy for Improving Land Administration in India - Deininger, Klaus (World Bank, Washington, DC, 2012)
In India, as in many developing countries, land continues to have enormous economic, social, and symbolic relevance. How access to land can be obtained, and how ownership of land can be documented, are questions essential to the livelihoods of the large majority of the poor, especially in rural and tribal areas. Answers to these questions will determine to what extent India's increasingly scarce natural resources are managed. Moreover, land policy and administration are critical determinants of the transaction costs associated with accessing and transferring land, both for business and residential use. This will affect how easily land can be used as collateral for credit and the development of the financial sector. Land continues to be a major source of government revenue through stamp duties, and is a key element in implementing a wide range of government programs. Land policies and institutions will have a far-reaching impact on the country's ability to sustain high rates of growth, on the degree that economic growth benefits the poor, and on the level and spatial distribution of economic activity. To make progress towards the long term goal of improved land administration and policy in India, a number of immediate steps are recommended. First, expand computerization and integration and use of textual records to ensure full coverage. Second, establish a spatial framework capable of achieving full coverage with reasonable time and resource requirements, at lest in the medium term. Third, pilot ways to improve textual and spatial records for well-defined situations to establish processes that can be scaled up rapidly, improving textual and spatial records. Fourth, allow private sector participation in surveying, focusing government on a regulatory role, reduce stamp duty rates, and explore the scope for replacing them with a land tax.